The Influence of Industrial Specialization Auditor on Audit Report Lag - Monique, Angelia; Harymawan, Iman (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2022)
This study aimed at analyzing the impact of Industrial specialization auditor on audit report lag and how the related party transaction affects the relationship between Industrial specialization auditor and audit report lag. This study used 1,897 observations from 353 different firms listed on the Indonesia Stock Exchange from 2010 to 2017. Industrial specialization auditor was measured using market share based on total assets. This study used an Ordinary Least Square Regression analysis model. This study found that firms audited by the industrial specialization auditors had shorter audit report lag. This study also found that firms with high disclosure of the related party transactions had shorter audit report lag and those audited by the industrial specialization auditors belonging to the related party transactions did not extend (shorten) the audit report lag. These results indicate that firms audited by the industrial specialization auditors influenced the audit report lag; firms with high disclosure of the related party transactions influenced the audit report lag; and firms audited by the industrial specialization auditors belonging to high related party transactions did not influence the audit report lag. The implication of this study can be used by the firm management as a consideration in selecting the auditors.